Standardised patient education in adrenal insufficiency: a prospective multi-centre evaluation. Issue 2 (August 2020) - Burger-Stritt, Stephanie; Eff, Annemarie; Quinkler, Marcus; Kienitz, Tina; Stamm, Bettina; Willenberg, Holger S; Meyer, Gesine; Klein, Johannes; Reisch, Nicole; Droste, Michael; Hahner, Stefanie
Abstract : Objective: Patients with adrenal insufficiency (AI) suffer from impaired quality of life and are at risk of adrenal crisis (AC) despite established replacement therapy. Patient education is regarded an important measure for prevention of AC and improvement of AI management. A standardized education programme was elaborated for patients with chronic AI in Germany. Design: Longitudinal, prospective, questionnaire-based, multi-centre study. Methods: During 2-h sessions, patients ( n  = 526) were provided with basic knowledge on AI, equipped with emergency cards and sets and trained in self-injection of hydrocortisone. To evaluate the education programme, patients from eight certified centres completed questionnaires before, immediately after and 6–9 months after training. Results: 399 completed data sets were available for analysis. Questionnaire score-values were significantly higher after patient education, indicating successful knowledge transfer (baseline: 17 ± 7.1 of a maximum score of 29; after training: 23 ± 4.2; P  < 0.001), and remained stable over 6–9 months. Female sex, younger age and primary cause of AI were associated with higher baseline scores; after education, age, cause of AI and previous adrenal crisis had a significant main effect on scores. 91% of patients would dare performing self-injection after training, compared to 68% at baseline. An improvement of subjective well-being through participation in the education programme was indicated by 95% of the patients 6–9 months after participation. Conclusion: Patient group education in chronic AI represents a helpful tool for the guidance of patients, their self-assurance and their knowledge on prevention of adrenal crises. Repeated training and adaptation to specific needs, for example, of older patients is needed.